Impact of non nutritional factors on milk urea concentration and its relationship with production and fertility traits in Vojvodina dairy herds - Ksenija Čobanović; Denis Kučević; Miroslav Plavšić; Vladan Bogdanović (Mljekarstvo)
The purpose of this study was to examine possible relationship between milk urea and fertility of dairy cows using field data. This study also evaluated the influence of environmental factors on milk urea (MU) and the relationship between MU and daily milk yield, milk fat and protein percentage. The data were collected at 11 dairy farms in the Vojvodina region. Reproductive dana and MU measurements were obtained from cows that calved between June 2013 and October 2015 and had a successful conception after calving. Statistical data processing was carried out by applying General Linear Model procedure, Statistics 13. Parity, calving season, season of milk control and farm were included in the models as fixed effects. Significant differences in MU concentrations were observed between farms (P<0.01), seasons (P<0.01) and parity (P<0.05). Highly significant (P<0.01) positive relationships were found between MU concentration and milk yield, fat and protein percentage and days open. Cows with MU levels below 10 mg dL-1 had the lowest day open interval (135.59 days) and cows with MU higher than 35 mg dL-1 had the longest days open interval (163.18 days). The cows with the lowest mean MU values (< 10 mg dL-1), had the shortest days open interval (72.62 days), but cows with mean MU values between 20.01-25.00 mg dL-1 had the longest days open interval (161.78 days). Results of this study indicate that increased MU levels appear to have a negative effect on dairy cow fertility.